Ask a New Question
Search
prove that if cotx(1+sinx)=4m and cotx(1-sinx)=4n, then (m^2-n^2)^2=mn
My previous question:
Verify that (secx/sinx)*(cotx/cscx)=cscx is an identity. (secx/sinx)*(cotx/cscx) = (secx/cscx)(cotx/sinx) =
2 answers
asked by
Jon
896 views
The equation 2sinx+sqrt(3)cotx=sinx is partially solved below.
2sinx+sqrt(3)cotx=sinx sinx(2sinx+sqrt(3)cotx)=sinx(sinx)
7 answers
asked by
girly girl
5,583 views
2)Prove the following identities:
a)(cosecx + cotx)(cosecx - cotx) = cotxtanx b)2/1+sinx + 1/1-sinx = 3sec^2x - tanxcosecx
3 answers
asked by
sweetG
664 views
express this in sinx
(1/ cscx + cotx )+ (1/cscx- cotx) i got 2sinx is that right?? and B) express in cosx problem: is 1 +
1 answer
asked by
linds
1,381 views
Prove that if y = cotx then dy/dx = - (cscx)^2. Hint: cotx = cosx/sinx
1 answer
asked by
help me pls
427 views
How would you prove/Verify this Identity.
x=theta (cosx+sinx-sin^3x)/(sinx)=cotx+cos^2x
1 answer
asked by
Beatrice
550 views
prove that if cotx(1+sinx)=4m and cotx(1-sinx)=4n, then (m^2-n^2)^2=mn
0 answers
asked by
krishan
426 views
Prove the following:
[1+sinx]/[1+cscx]=tanx/secx =[1+sinx]/[1+1/sinx] =[1+sinx]/[(sinx+1)/sinx] =[1+sinx]*[sinx/(sinx+1)]
3 answers
asked by
Anonymous
917 views
Verify the identity .
(cscX-cotX)^2=1-cosX/1+cosX _______ sorry i cant help you (cscX-cotX)=1/sinX - cosX/sinX = (1-cosX)/sinX If
0 answers
asked by
Rose
699 views
Prove the identity
cscx+cotx-1/cotx-cscx+1 = 1+cosx/sinx
3 answers
asked by
Anonymous
1,710 views